Effect of Ultrasonic Assisted Extraction with Ethanol for Removing Lipid on Catfish (Pangasius sp.) Skin as a Collagen Source and Its Characteristics - Agustina, Maulida; Patmawati, Patmawati; Mubarok, Shofy; Sulmartiwi, Laksmi; Wulandari, Diah Anggraini; Zai, Khadijah; Siva, Raseetha; Pujiastuti, Dwi Yuli; Nirmala, Dwitha; Carattri Kusuma Werdani, Money; Moechthar, Oemar; Alwi Husein, Mohamad Akmal (Jurnal Ilmiah Perikanan dan Kelautan, 2024)
Abstract Fish skin is rich in collagen (80%-90%). However, catfish (Pangasius sp.) skin has a high lipid content, which can reduce the quality of collagen. Therefore, treatment is needed to remove the lipid using ultrasonic assisted extraction (UAE) with ethanol. Hence, the aim of the present study was to remove lipid content from catfish skin as a raw material for collagen by using UAE with different concentrations of ethanol (25, 50, and 75%). The research was conducted in three stages: removing impurities, collagen extraction, and characterization of collagen. The result exhibited that UAE-ethanol treatment was capable of removing up to 85.6% of lipid content, and the produced collagen had the potential to be utilized as an alternative source of collagen based on its properties. Highlight Research Ethanol could be used as extractor of lipid from catfish skin of Pangasius Ultrasonic assisted extraction could increase efficiency of lipid extraction from catfish skin. Fish skin of Pangasius sp. has a potential source for collagen. Collagen from skin of Pangasius sp. has a good characteristic with high protein content.